History of Culture and Tourism in DKI Jakarta Through Time - Kusumastuti, Frida Restu Rizki; Nuraulia, Resti Eka; Haerunisah, Efa; Nasiatul , Asrit; Mutmainah, Mutmainah; Aulia, Nabiilah; Gustina, Pinkit Imeli; Renita, Renita; Dewi, Ratna (Educative: Jurnal Ilmiah Pendidikan, 2025)
DKI Jakarta, from the era of the Sunda Kelapa Kingdom to the modern day, has been the nation's capital, spanning Dutch colonial rule and the independence period. As the centre of government and culture, Jakarta possesses complex historical dynamics and exerts a significant influence on national identity. This study employs a descriptive qualitative approach, with a literature review serving as the primary method. The results indicate that Jakarta has experienced a major cultural transformation due to the acculturation of diverse ethnicities and cultures, including Betawi, Chinese, Arabic, and Dutch. Additionally, the development of tourism in Jakarta is greatly influenced by its historical heritage and local cultural assets, as reflected in destinations such as the Old City, the National Monument, museums, and art and cultural centres. The role of government and society in preserving cultural values and promoting tourism is crucial to maintaining the city's identity and ensuring its sustainability. This study underscores the importance of integrating history and culture into tourism planning to establish Jakarta as a global city that remains anchored in its local heritage.